Improving the seismic hazard evaluation of the Lisbon and Lower Tagus Valley area - Carvalho, João P. F. (2009)
The Lisbon and surrounding area of the Lower Tagus Valley has experienced in the past the effects of several moderate sized earthquakes that caused significant damage and destruction. They have been attributed to local sources, though in some cases the source remains to be located. The lack of outcrops in the flat lying Quaternary terrains, the low slip-rates of the area in connection with sedimentation and erosion rates that erase surface ruptures are among the causes of a poor association between faults and seismicty, which has opened way to geophysical studies. Seismic, potential-field and seismicity data have been recently used to improve the seismic hazard evaluation of the area. In this work we complement these studies with DTM and PSInSAR data with the purpose of obtaining an accurate evaluation of the seismic hazard of the study area. The correlation of improved epicentre locations with major fault zones located from the above mentioned data shows that we have progressed in the understanding of the earthquake sources in the region. Some structures show no apparent relationship with present-day seismicity but some are known to be active into the Quaternary. Further geophysical and geological studies are required to understand the causes.